Bowling Together: On Selected Aspects of Professional Capital in 21st Century Education - Herzog, Tomasz (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Professional Capital, Professional Communication, Civic Participation, and Community are the ideas about teachers as social change agents that have recently come into particular focus in thinking about today’s education. In the first part of this paper these ideas are examined in their broad political, social, cultural, and economic contexts. The second part looks more closely at the important aspects of communication and their implications for education and educators.